2022
DOI: 10.1186/s13045-022-01261-z
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of RNA sensors in tumor microenvironment and immunotherapy

Abstract: RNA sensors detect foreign and endogenous RNAs to protect the host by initiating innate and adaptive immune response. In tumor microenvironment (TME), activation of RNA sensors induces tumor-inhibitory cytotoxic T lymphocyte responses and inhibits the activity of immunosuppressive cells though stimulating type I IFN signaling pathway. These characteristics allow RNA sensors to be prospective targets in tumor immunotherapy. Therefore, a comprehensive understanding of the roles of RNA sensors in TME could provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 178 publications
0
14
0
Order By: Relevance
“…RIG-I is well established to be one of the critical intracellular sensors for host recognition of RNA virus infection and subsequent induction of type I interferon (IFN) production in innate immune cells. It contains a C-terminal helicase domain to recognize cytoplasmic viral RNA and two N-terminal tandem caspase-recruiting domains (CARDs) to activate downstream type I IFN production [ 11 , 12 ]. Other than RIG-I expression in immune cells, we previously found that RIG-I expression was mainly located in parenchymal hepatocytes in the liver, but not in mesenchymal cells [ 13 ], suggesting the potential roles of RIG-I in liver functions and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…RIG-I is well established to be one of the critical intracellular sensors for host recognition of RNA virus infection and subsequent induction of type I interferon (IFN) production in innate immune cells. It contains a C-terminal helicase domain to recognize cytoplasmic viral RNA and two N-terminal tandem caspase-recruiting domains (CARDs) to activate downstream type I IFN production [ 11 , 12 ]. Other than RIG-I expression in immune cells, we previously found that RIG-I expression was mainly located in parenchymal hepatocytes in the liver, but not in mesenchymal cells [ 13 ], suggesting the potential roles of RIG-I in liver functions and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of MDA5-MAVS pathway in tumor immunity is still very complex, and many questions remain unanswered. Recently, increasing evidences have illustrated how the innate immune pathway in the tumor microenvironment changes tumorigenesis in different tumors, thus affecting the subsequent design of effective immunotherapy trials ( 83 , 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…LGP2 may repress RIG-I signaling through multiple mechanisms, such as interruption of the interaction between RIG-I and MAVS [45,46], inhibition of Dicer processing of long dsRNA [47], prevention of viral dsRNA binding to RIG-I [48], and suppression of TRIM25-mediated RIG-I ubiquitination [49]. On the other hand, accumulating evidence indicates that LGP2 cooperates with MDA5 to augment IFN response [50][51][52]. LGP2 promotes MDA5 nucleation and the conversion of MDA5 to an active conformation [50].…”
Section: An Overview Of Rlrs Signalingmentioning
confidence: 99%